Human brucellosis in pregnancy - an overview - Bosilkovski, Mile; Arapović, Jurica; Keramat, Fariba (Association of Basic Medical Sciences of FBIH, 2020)
Human brucellosis during pregnancy is characterized by significantly less pronounced adverse obstetric outcomes than in animals, but with remarkably more adverse obstetric outcomes when compared to healthy pregnant women. Seroprevalence of brucellosis in pregnancy and cumulative incidence of brucellosis cases per 1000 delivered obstetrical discharges in endemic regions were reported to be 1.5-12.2% and 0.42-3.3, respectively. Depending on the region, the frequency of pregnant women in the cohorts of patients with brucellosis was from 1.5% to 16.9%. The most common and the most dramatic unfavorable outcomes during brucellosis in pregnancy are the obstetric ones, manifested as abortions (2.5-54.5%), intrauterine fetal death (0-20.6%), or preterm deliveries (1.2-28.6%), depending on the stage of pregnancy. Other unfavorable outcomes due to brucellosis are addressed to infant (congenital/neonatal brucellosis, low birth weight, development delay, or even death), the clinical course of disease in mother, and delivery team exposure. When diagnosed in pregnant women, brucellosis should be treated as soon as possible. Early administration of adequate therapy significantly reduces the frequency of adverse outcomes. Rifampicin in combination with trimethoprim-sulfamethoxazole for 6 weeks is the most commonly used and recommended regimen, although monotherapies with each of these two drugs are also widely used while waiting for the results from prospective randomized therapeutic trials. As no effective human vaccine exists, screening of pregnant women and education of all women of childbearing age about brucellosis should be compulsory preventive measures in endemic regions.